2019
DOI: 10.1136/bmj.l6762
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision making: why the slow progress? An essay by Neal Maskrey

Abstract: After more than 40 years of research and policy endorsement, adoption of shared decision making into routine practice has been remarkably slow. Neal Maskrey blames a lack of focus on doctors’ broader communication skills

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…5 It involves training physicians and other healthcare professionals in SDM communication skills as well as encourage patients to actively participate in communication, in addition to providing evidence-based, easy to understand information on treatment alternatives to patients and their physicians. 8 To be effective in daily practice, SDM should be codesigned with involved stakeholders to gain acceptance and recognition. 3 In addition, it needs an inner (ie, within the institution that wants to do SDM) and an outer (concerning the external conditions in which the institution works) settings, in which programme implementation is possible, as defined, for example, by the Consolidated Framework for Implementation Research (CFIR) (see table 1 for this project).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…5 It involves training physicians and other healthcare professionals in SDM communication skills as well as encourage patients to actively participate in communication, in addition to providing evidence-based, easy to understand information on treatment alternatives to patients and their physicians. 8 To be effective in daily practice, SDM should be codesigned with involved stakeholders to gain acceptance and recognition. 3 In addition, it needs an inner (ie, within the institution that wants to do SDM) and an outer (concerning the external conditions in which the institution works) settings, in which programme implementation is possible, as defined, for example, by the Consolidated Framework for Implementation Research (CFIR) (see table 1 for this project).…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…There appears to be room for improvement with respect to readability and accessibility of existing tools [22]. However, it has also been suggested that a broader approach may be needed to improve uptake of shared decisionmaking, for example focusing on communication skills and changing consultation models such that shared understanding of problems, and patient priorities and preferences are central to decision-making [23,24].…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 99%
“…Maskrey asks why progress in shared decision making has been slow 1. Medicine has ignored insights from conversation analysis and sociolinguistics.…”
mentioning
confidence: 99%